Profit Maximization Using Prediction Model (International Journal of Engineering and Computer Science, 2014)
The objective of this contest is to maximize the profit using metric by which classifier’s performance will be tested and applied to customer churn problems which will be driven by classifiers i.e. customer churn prediction model. The public dataset that has customer usage pattern and if the customer has churned or not ,these factors will be applied to our profit maximizing framework. With the explosive growth of data, and the increasing popularity of social network sites, companies will rely more than ever on data mining techniques to support their decision making process. In such cases, the cost-benefit analysis framework provides directions on how to develop performance measures tailored to specific business problems